Pentashihan dan Para Pentashih Mushaf Al-Qur'an di Indonesia, 1957-2020 - Zaenal Arifin Madzkur; Mustopa Mustopa; Irwan Irwan (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
This writing explains the correction and the correctors of the mushaf in Indonesia since before the establishment of the Board of Mushaf Correction (Lajnah Pentashihan Mushaf Al-Qur'an ) in 1957 to 2020. The mushaf that will be printed should be corrected first to avoid the mistakes and to keep its authenticity. By using historical approach, it is known that the pattern of correction is getting more and more developed by the way of studying literatures related to the writing of the mushaf to that of comparing the mushaf that will be printed with the manuscript of the Indonesian Standard Qur’an. The pattern of the appointment of the corrector of the mushaf is also a dynamic one. Starting from the individual appointment, organization of society, to the official appointment by the state through the Board of Correction of the Mushaf in 2007. The Board of Correction of the Mushaf (Lajnah Pentashihan Mushaf Al-Qur'an ) is a working task force under the Board of Research and Development and the Education and Training of the Ministry of Religious Affairs. The Mushafs being produced are also various, starting from the mushaf that only put the Qur’anic text, mushaf with translation, mushaf with the tajwid (the rules of reading the Qur’an), mushaf with word per word translation to the mushaf with some additional texts which all are adding the development of the Qur’anic publication in Indonesia.